Accounting-policy choice and firm characteristics in the Asia pacific region: an international empirical test of costly contracting theory - Astami, E.; Tower, Greg (Elsevier, 2006)
This study provides evidence on the cross-sectional relationship between firm-specific variables and management's choice of accounting policies by examining four key accounting-policy disclosures in the 2000/2001 annual reports of 442 listed companies in the Asia Pacific region. The dependent variable is the composite measure for the income increasing (decreasing) accounting-policy choice tendency. The results show that firm-specific variables linked to Costly Contracting Theory partially explain management's choice of accounting policies. Companies that pursue income-increasing accounting techniques are characterized by lower financial leverage, lower level of ownership concentration, and higher investment opportunity sets. This finding holds true when country and industry control variables are not considered. When the control variables are included, the CCT variables are less a factor and instead country of reporting provides the strongest explanation for company managers' choice of accounting policies. Indonesian companies utilize the most income-decreasing accounting technique.